Living Hadis dan Budaya Konsumsi Kontemporer: Negosiasi Nilai-Nilai Keagamaan dalam Praktik Makan dan Minum Sambil Berdiri pada Pesta Pernikahan: Living Hadith and Contemporary Consumer Culture: The Negotiation of Religious Values in the Practice of Eating and Drinking While Standing at Wedding Receptions - Supriyanto; Nasrulloh (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
This study aims to examine the negotiation of religious values in contemporary consumer culture through the perspective of Living Hadith regarding the practice of eating and drinking while standing at wedding receptions. The phenomenon of standing parties represents a transformation in consumer culture influenced by modernization, demands for social efficiency, and changes in the lifestyles of urban communities. The study employs a qualitative approach using a case study design within the Living Islam perspective. Data were collected through observation and documentation involving wedding organizers, religious figures, and the Muslim community. Data analysis was conducted through the stages of data reduction, thematic categorization, and socio-religious interpretation. The research findings indicate that standing parties are viewed as symbols of modernity, flexibility, and practicality in wedding receptions. Muslim communities negotiate religious values by reinterpreting the etiquette of eating and drinking based on social contexts and contextual religious understandings. The transformation of consumption etiquette represents a form of negotiation between Islamic values and modern social change. Through the process of reinterpreting teachings and consumption practices, the community strives to preserve religious values while adapting them to the needs and dynamics of contemporary life, thereby maintaining religious normative legitimacy within an ever-evolving cultural context.